Sulfur degassing at Erta Ale (Ethiopia) and Masaya (Nicaragua) volcanoes: Implications for degassing processes and oxygen fugacities of basaltic systems1. (2nd October 2013) - de Moor, J. M.; Fischer, T. P.; Sharp, Z. D.; King, P. L.; Wilke, M.; Botcharnikov, R. E.; Cottrell, E.; Zelenski, M.; Marty, B.; Klimm, K.; Rivard, C.; Ayalew, D.; et al.
Abstract : [1] We investigate the relationship between sulfur and oxygen fugacity at Erta Ale and Masaya volcanoes. Oxygen fugacity was assessed utilizing Fe 3+ /∑Fe and major element compositions measured in olivine‐hosted melt inclusions and matrix glasses. Erta Ale melts have Fe 3+ /∑Fe of 0.15–0.16, reflecting f O2 of ΔQFM 0.0 ± 0.3, which is indistinguishable from f O2 calculated from CO2 /CO ratios in high‐temperature gases. Masaya is more oxidized at ΔQFM +1.7 ± 0.4, typical of arc settings. Sulfur isotope compositions of gases and scoria at Erta Ale (δ 34 Sgas  − 0.5‰; δ 34 Sscoria  + 0.9‰) and Masaya (δ 34 Sgas  + 4.8‰; δ 34 Sscoria  + 7.4‰) reflect distinct sulfur sources, as well as isotopic fractionation during degassing (equilibrium and kinetic fractionation effects). Sulfur speciation in melts plays an important role in isotope fractionation during degassing and S 6+ /∑S is <0.07 in Erta Ale melt inclusions compared to >0.67 in Masaya melt inclusions. No change is observed in Fe 3+ /∑Fe or S 6+ /∑S with extent of S degassing at Erta Ale, indicating negligible effect on f O2, and further suggesting that H2 S is the dominant gas species exsolved from the S 2− ‐rich melt (i.e., no redistribution of electrons). High SO2 /H2 S observed in Erta Ale gas emissions is due to gas re‐equilibration at low pressure and fixed f O2. Sulfur budget considerations indicate that the majority of S injected into the systems is emitted as gas, which is therefore representative of the magmatic S isotope composition. The composition of the Masaya gas plume (+4.8‰) cannot be explained by fractionation effects but rather reflects recycling of high δ 34 S oxidized sulfur through the subduction zone. Key Points: Oxygen fugacity is buffered during degassing of basalts Sulfur isotope fractionation is an equilibrium and kinetic process Sulfur isotopes of arc gases indicate contribution from subducted sulfate